2019
DOI: 10.2528/pierc19080806
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Bonding Points on Metal Surface-Mounted FBG Sensors for Electric Machines

Abstract: Fibre Bragg Gratings (FBGs) offer several advantages including their immunity to electromagnetic fields making them excellent in situ sensors for feature extraction in electrical machines condition monitoring. However, the pre-requisite of bonding FBGs circumferentially on either the machine cast frame or stator windings can introduce undesired sensing characteristics. This is because the FBG relies on adhesives as the transfer medium for any sensed parameter between the machine and sensor. Whilst FBG sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The FFT on the stray flux revealed a significant difference in spectral content, but also a consistency in these differences. For instance, when the motor was run at odd frequencies (5, 15, and 25 Hz), the stray flux under the broken rotor condition consistently showed a significant variation in its time varying amplitude, compared to the variations observed when the motor was run at even frequencies (10,20,and 30 Hz). This behavior may have been due to the forced vibration characteristics of the motor at odd frequencies compared to even frequencies, which would require vibration analysis, which is beyond the scope of this work.…”
Section: Fbg-t Fault Severity Discriminationmentioning
confidence: 94%
See 1 more Smart Citation
“…The FFT on the stray flux revealed a significant difference in spectral content, but also a consistency in these differences. For instance, when the motor was run at odd frequencies (5, 15, and 25 Hz), the stray flux under the broken rotor condition consistently showed a significant variation in its time varying amplitude, compared to the variations observed when the motor was run at even frequencies (10,20,and 30 Hz). This behavior may have been due to the forced vibration characteristics of the motor at odd frequencies compared to even frequencies, which would require vibration analysis, which is beyond the scope of this work.…”
Section: Fbg-t Fault Severity Discriminationmentioning
confidence: 94%
“…This is mainly because optical fibers are inherently immune to electromagnetic fields; hence the use of terfenol-D in this research, as shown in Figure 2. Prior to carrying out experiments, the effect of the number of bonding points on the metal surface-mounted FBG sensors was investigated and reported in [20], which took account of the impact of the adhesive used.…”
Section: Basic Fbg Sensing Principlementioning
confidence: 99%
“…The performance of surface strain sensing using FBG technology can be affected by the utilized bonding material and mounting procedure [41]. Different bonding methods have been explored in literature, ranging from application of cyanoacrylate adhesive and epoxy-resin glue [42], [43] to use of polyamide tape [19], [43]. While the former methods can provide increased rigidity and thus load to sensor transfer, they also impose a generally more complicated installation procedure and are fixed with no flexibility in terms of sensor repositioning and re-application.…”
Section: Fbg Strain Sensing Principlesmentioning
confidence: 99%
“…Based on works from [1][2][3][4][5][6] there are recent suggestions that FBG does possess encouraging potential for sensing applications in non-permanent magnet machines especially, induction machine and hydro generators. Applications in power electronics modules, multipoint voltage sensing and machine mechanical parameter monitoring such as bearings [7][8][9][10][11][12] have also been reported. FBG sensing is based on the variation of the refractive indices of the fibre core and cladding due to variations in some sensed parameter.…”
Section: Introductionmentioning
confidence: 99%